CAN TED TALK TRANSCRIPTS SERVE AS EXTENSIVE READING MATERIAL FOR MID-FREQUENCY VOCABULARY LEARNING? - Hsu, Wenhua (TEFLIN Journal, 2020)
Schmitt and Schmitt (2014) labeled the first 4000 to 9000 word families as mid-frequency words and stressed their importance based on Nation’s (2006) estimate that for adequate comprehension of a variety of authentic texts, knowledge of the first 9000 word families is necessary. Subsequent to this vocabulary goal is to determine what can be read extensively to increase vocabulary progressively since most words cannot be mastered through only one exposure. This research aimed to investigate how much TED talk transcripts input is needed to encounter most of the first 9000 word families for learning to occur. It first measured the vocabulary levels of TED talks for their potential as extensive reading material for mid-frequency word learning. The results show that TED talks reached the 5th to 6th 1000-word-family level at 98% lexical coverage. Corpus sizes of 0.3 to 4.8 million words of TED transcripts provided an average of 12+ repetitions for most of the words from the first 4th to 9th 1000 word families. The figures may serve as a reference for learners in extensive reading programs to decide how much effort they should make to read TED talk transcripts voluminously to reach a certain vocabulary goal.